Analysis of Green Building Implementation in the Southeast Minahasa Regent's Office Building Based on the Greenship Existing Building Rating Tool - Deisi Grasye Porajow, Regina; Sumajouw, M. D. J.; Mangangka, Isri R. (PT ARRUS Intelektual Indonesia, 2023)
Southeast Minahasa Regency increase the construction of infrastructure and buildings in every year. This development certainly resulted in major changes in the surrounding environment. This is the basis for this study to evaluate the Southeast Minahasa Regent's Office building based on the Greenship Existing Building. This research aims to evaluate the implementation of green buildings in the Southeast Minahasa Regent's Office building, then provide recommendations for improvements in aspects that have yet to be achieved without changing the structural and architectural aspects of the building. Based on the evaluation results of six aspects in the Greenship Existing Building version 1.1 criteria, Southeast Minahasa Regent’s Office building received a total score of 18 points or 15.38% of a maximum of 117 points. Thus, the Southeast Minahasa Regent's Office building does not meet the criteria as a green building concept, and it is necessary to provide recommendations in order to meet the green building criteria.